Senkung des Fluoridgehaltes im Krill durch Behandlung mit Säuren - Manthey, Monika; Schreiber, W. (1983)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010